The mysticism scale as a measure for subjective spirituality: new results with Hood's M-Scale and the development of a short form - Streib, Heinz (Assessing Spirituality in a Diverse World, 2021)
In this chapter, we suggest the use of Hood’s Mysticism Scale (M-scale) for a differential assessment of subjective spirituality. We base this view on the conceptualization of mysticism and its relation to spirituality, and on the definition of spirituality as individualized experience-orientated religiosity. This perspective was empirically tested in the Bielefeld-based Cross-cultural Study on Spirituality, which explored in comprehensive semantic analyses how participants in the USA and Germany define spirituality and revealed that more spiritual than religious people preferably associate spirituality with experiences of all-connectedness, search for a higher self, existential truth, and humanistic morality. Moreover, structural equations modeling based on this and other recent data sets reveal that the M-scale and its factors have considerable effects on self-rated spirituality. Thus, we recommend the M-scale as measure for subjective spirituality, which avoids the widespread problem of many extant measures that assess spirituality primarily in terms of either (Christian) religiosity or psychosocial well-being. The M-scale may be very useful in research that intends to assess the subjective spirituality of a diversity of participants who might affiliate with various religious traditions and worldviews, including the non-religious, atheists, and non-theists. Besides the well-established 32-item version of the M-scale, the chapter additionally presents an economic 8-item short form of the M-scale and its psychometric properties.